A Selective Protection Scheme for Scalable Video Coding - Kim, H.; Munchurl Kim (IEEE transactions on circuits and systems for video technology, 2011)
Selective protection can exploit dependency coding properties to effectively perform partial protection on scalable video coding (SVC) bitstreams since protecting frames in lower scalability layers affects visual quality of the reconstructed frames in higher scalability layers. In this paper, we propose a selective protection scheme that maximizes protection effects by the minimum number of encoded frames to be protected in the SVC bitstream domain. We first model the SVC dependency coding structure as a directed acyclic graph which is characterized with an estimated visual quality value as the attribute at each node. In addition, a visual quality estimation model is proposed based on the proportions of intra-predicted and inter-predicted MBs, amounts of residues, and estimated visual quality of reference frames. The proposed selective protection scheme traverses the dependency graph to find optimal protection paths that can give the maximum visual quality degradation. Experimental results show that, compared to the existing protection schemes, the proposed selective protection scheme reduces computation complexity in the number of protected frames, the amount of protected data, and the protection time saving. The SVC file format specification supports the carriage of selectively protected bitstreams based on the concept of our selective protection in dependency coding structure of SVC.